Solve by using quadratic formula:
![8. \: 5{}^{2x - 1 } + 5 {}^{ x+ 1} = 250 8. \: 5{}^{2x - 1 } + 5 {}^{ x+ 1} = 250](https://tex.z-dn.net/?f=8.+%5C%3A+5%7B%7D%5E%7B2x+-+1++%7D++%2B+5+%7B%7D%5E%7B+x%2B+1%7D++%3D+250)
Ans: 2
Class 10
Content Quality Solution Required
❎ Don't Spamming ❎
Answers
Answered by
2
Discriminant = b² - 4ac
=> (25)² - 4(5)(-1250)
=> 625 + 5000
=> 5625
Hence, applying quadratic equation,
![t = \frac{ - b + \sqrt{d} }{2a} \: \: \: \: or \: \: \: \: \: t= \frac{ - b - \sqrt{d} }{2a} \\ \\ \\ => t = \frac{ - 25 + \sqrt{5625} }{2(1)} \: \: \: or \: \: \: \: t= \frac{ - 25 - \sqrt{5625} }{2(1)} \\ \\ \\ = > t = \frac{ - 25 + 75}{2} \: \: \: \: \: or \: \: \: \: \: t= \frac{ - 25 - 75}{2} \\ \\ \\ => t= \frac{50}{2} \: \: \: or \: \: \: \: \: t = \frac{ - 100}{2} \\ \\ \\ \\ t = 25 \: \: \: or \: \: \: t= -50 t = \frac{ - b + \sqrt{d} }{2a} \: \: \: \: or \: \: \: \: \: t= \frac{ - b - \sqrt{d} }{2a} \\ \\ \\ => t = \frac{ - 25 + \sqrt{5625} }{2(1)} \: \: \: or \: \: \: \: t= \frac{ - 25 - \sqrt{5625} }{2(1)} \\ \\ \\ = > t = \frac{ - 25 + 75}{2} \: \: \: \: \: or \: \: \: \: \: t= \frac{ - 25 - 75}{2} \\ \\ \\ => t= \frac{50}{2} \: \: \: or \: \: \: \: \: t = \frac{ - 100}{2} \\ \\ \\ \\ t = 25 \: \: \: or \: \: \: t= -50](https://tex.z-dn.net/?f=t+%3D+%5Cfrac%7B+-+b+%2B+%5Csqrt%7Bd%7D+%7D%7B2a%7D+%5C%3A+%5C%3A+%5C%3A+%5C%3A+or+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+t%3D+%5Cfrac%7B+-+b+-+%5Csqrt%7Bd%7D+%7D%7B2a%7D+%5C%5C+%5C%5C+%5C%5C+%3D%26gt%3B+t+%3D+%5Cfrac%7B+-+25+%2B+%5Csqrt%7B5625%7D+%7D%7B2%281%29%7D+%5C%3A+%5C%3A+%5C%3A+or+%5C%3A+%5C%3A+%5C%3A+%5C%3A+t%3D+%5Cfrac%7B+-+25+-+%5Csqrt%7B5625%7D+%7D%7B2%281%29%7D+%5C%5C+%5C%5C+%5C%5C+%3D+%26gt%3B+t+%3D+%5Cfrac%7B+-+25+%2B+75%7D%7B2%7D+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+or+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+t%3D+%5Cfrac%7B+-+25+-+75%7D%7B2%7D+%5C%5C+%5C%5C+%5C%5C+%3D%26gt%3B+t%3D+%5Cfrac%7B50%7D%7B2%7D+%5C%3A+%5C%3A+%5C%3A+or+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+t+%3D+%5Cfrac%7B+-+100%7D%7B2%7D+%5C%5C+%5C%5C+%5C%5C+%5C%5C+t+%3D+25+%5C%3A+%5C%3A+%5C%3A+or+%5C%3A+%5C%3A+%5C%3A+t%3D+-50)
Neglect, t = -50
t = 25
5^x = 25
5^x = 5^2
x = 2
=> (25)² - 4(5)(-1250)
=> 625 + 5000
=> 5625
Hence, applying quadratic equation,
Neglect, t = -50
t = 25
5^x = 25
5^x = 5^2
x = 2
Attachments:
![](https://hi-static.z-dn.net/files/d80/61c8ef41ef1990558b002d1256f01db8.jpg)
![](https://hi-static.z-dn.net/files/db2/360b96e5b3dc12a81c6dacf4c56fd56c.jpg)
Answered by
3
Let 5^x = y.
= > y^2 + 25y - 1250 = 0
(1)
= > 25.
(2)
= > -100/2
= > -50.
Therefore the values are 25,-50.
Neglect -ve values. Then the value is y = 25.
Now,
= > 5^x = 25
= > 5^x = 5^2
= > x = 2.
Hope this helps!
siddhartharao77:
:-)
Similar questions